THE INFLUENCE OF AWARDS, TRANSFORMATIONAL LEADERSHIP, COMMUNICATION, AND MOTIVATION ON THE PERFORMANCE OF BIREUEN DISTRICT REGIONAL DISASTER MANAGEMENT AGENCY EMPLOYEES - Chairul Bariah; Hayanuddin Safri; Sri Yanna; Sutoyo Sutoyo (SEAN Institute, 2023)
This type of research is quantitative. The place of this research is the Regional Disaster Management Agency of Bireuen Regency. This study's population consisted of 90 employees of the Bireuen District Regional Disaster Management Agency. The sampling technique used is saturated sampling. The analysis used is multiple linear regression. The regression analysis results obtained a t count value of 1.893 > t table 1.6629. This means that the award variable (X1) positively affects the employee performance variable (Y). Based on the results of the regression analysis, it was obtained that the t value was 3.437 > t table 1.6629. This means that the transformational leadership variable (X2) positively affects employee performance variables (Y). Furthermore, the regression analysis results obtained a t value of 2.667 > t table 1.6629. This means that the communication variable (X3) positively affects employee performance variables (Y). The results of the regression analysis obtained a t value of 2.648 > t table 1.6629, which means that the motivation variable (X4) has a positive effect on employee performance variables (Y). The Fcount value is 35.157> Ftable 2.48 with a significance value of 0.000 <0.05. From these results, it can be concluded that Reward (X1), Transformational Leadership (X2), Communication (X3), and Motivation (X4) simultaneously have a positive and significant effect on employee performance (Y). The R Square value from the analysis of the coefficient of determination is 0.623, meaning that employee performance can be explained by the variables Reward (X1), Transformational Leadership (X2), Communication (X3), and Motivation (X4) of 62.3%. The remaining 37.7% can be explained by other variables not examined in this study.